Modelo experimental de carcinoma mamário em ratas induzidas com 7,12-dimetilbenz(a)antraceno. - Rezende, Laura Ferreira de; Costa, Eunice Cristina da Silva; Schenka, Natália Guimarães de Moraes; Schenka, André de Almeida; Untura, Lindsay Pâmela; Uemura, Gilberto [UNESP] (My University, 2010)
Objective: To test an experimental model of chemical mammary carcinogenesis induction in SpragueDawley rats. Methods: Thirty virgin Sprague-Dawley female rats, aged 50 days, received 20 mg of 7,12-dimethylbenz(a)anthracene (DMBA) intragastrically by gavage. At 12 week their mammary glands were examined. Brain, liver, bone and lung tissue were also analyzed. Results: Twelve weeks after DMBA injection, 85% rats presented at least one breast tumor. Conclusin: This experimental animal model of chemical mammary induced carcinogenesis is feasible and can be used in further experiments on the role of tumorigenic biomodulator substances.

Objetivo: Testar um modelo experimental de indução de carcinogênese em ratas Sprague-Dawley. Métodos: Foram estudadas 30 ratas fêmeas virgens Sprague-Dawley, induzidas ao carcinogênese mamário. Com 50 dias de vida, foi injetado 7,12-dimetilbenz(a)antrace no ventre por gavage. Com 12 semanas, as glândulas mamárias foram examinadas, assim como os tecidos cerebrais, pulmonares, ossos do fêmur e fígado. Resultados: Doze semanas após a injeção de DMBA, 85% das ratas apresentaram pelo menos um tumor mamário visível. Conclusão: O modelo experimental de carcinoma mamário induzido por DMBA mostrou-se efetivo e de fácil reprodução.
Induction of experimental mammary carcinogenesis in rats with 7,12-dimethylbenz(a)anthracene
Keywords: Breast neoplasms/chemically induced; 9,10-Dimethyl-1,2-benzanthracene/administration & dosage; Models, animal; Ratos; Neoplasias da mama/induzido quimicamente; 9,10-Dimetil-1,2-benzantraceno/administração & dosagem; Modelos animais; Ratas